2018
DOI: 10.2298/spat1839017c
|View full text |Cite
|
Sign up to set email alerts
|

Beyond formality: A contribution towards revising the participatory planning practice in Serbia

Abstract: Participation has been present in the Serbian legal framework in the domain of urban planning since the 1950s. Its scope and legal definition have evolved with the transition to democracy, markets and decentralised governance. In line with EU standards, Serbia introduced an additional level of participation in the form of early public inquiry in 2014. Still, participatory planning practice is often seen as a formality which lacks sufficient effect on the planning solution, and requires qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…The general assessment is that the awareness of the local population regarding cultural heritage is underdeveloped. In addition, Serbia as a post-socialist country, exemplifies a rather low level of active citizen participation in planning processes, with urban and spatial planning traditionally perceived as a task of the public sector [37].…”
Section: Local Community Engagementmentioning
confidence: 99%
“…The general assessment is that the awareness of the local population regarding cultural heritage is underdeveloped. In addition, Serbia as a post-socialist country, exemplifies a rather low level of active citizen participation in planning processes, with urban and spatial planning traditionally perceived as a task of the public sector [37].…”
Section: Local Community Engagementmentioning
confidence: 99%
“…In contrast, using Hungary as a case study in evaluating the importance of health technology assessment (HTA), Csanádi et al (2019) found that despite the HTA department fulfilling its duties as outlined in the legislation, the lack of stakeholder engagement meant limited transparency and openness. In this ever-changing environment, key planners of projects must be able to be flexible and address contemporary issues, thus in understanding that participatory planning practices in Serbia are often lackluster, Čolić and Dželebdžić (2018) suggest alternative methods of participation under the levels of informing, consulting, active participation and the two-way feedback informing that have yielded positive results in specific situations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the socialist planning era, public participation included methods such as the presentation of plans to local communities, questionnaires, expert discussions, public inquiry, and the possibility to submit a complaint that was reviewed by the designated planners (Nedović-Budić, Djordjević and Dabović, 2011). The domains of political, economic, and social transition, including that of collectivist ideology toward patterns of pluralism, went through radical changes with the transition from a socialist to a market-based economy (Čolić and Dželebdžić, 2018). However, the evolu-tion of the planning system in terms of practicing innovative and inclusive participation methods did not subsequently follow the socio-economic transition or technological pathways, until the COVID-19 pandemic influenced all spheres of life and work.…”
Section: Introductionmentioning
confidence: 99%
“…Given that public participation in Serbia is formally established as a normative basis that guarantees the rights of the public to participate in territorial development processes (Čolić and Dželebdžić, 2018), this work aims to identify contextual factors for digital participation in spatial planning within the scenario of MA as specific areas with rising attractiveness. The following chapter presents perspectives and limitations of digital public participation in urban and spatial planning worldwide.…”
Section: Introductionmentioning
confidence: 99%